The management strategy of the municipality in the context of current development challenges - Bernat, Piotr (Management and Administration Journal, 2025)
The article presents a discussion on the current situation of the municipalities, in the context of development. It highlights the key factors reflecting the needs and management capabilities of the municipality allowing for the formation of a rational functioning. It has been proposed to supplement the practical functioning of municipalities in the planning of the procedure, including a diagnosis of the current state and strategy, which ultimately enables management advantage. It presents the necessary changes in the management of the municipality in the context of coopetition enabling agreement with the competition. It discusses the related dilemmas and presents potential areas of cooperation.